Análise numérica da influência do tamanho e posicionamento de aberturas adjacentes a pilares de seção quadrada em sistemas estruturais de lajes lisas - Küster, Leandro Dias (2021)
The objective of the work was the theoretical and numerical study of the structural behavior of the reinforced concrete slab-column connection for models with different dimensions and opening positions close to the column. A wide bibliographic review on the subject was carried out, raising topics related to structural behavior, tests, numerical simulations and models of rupture load prediction. The methodology used consisted of calibrating a numerical reference model and subsequently a parametric study was carried out addressing the dimensions and positions of openings in a reference model, using the ABAQUS® software. In the numerical simulation it was verified the importance in the dilation angle, viscosity and refinement of the mesh to understand the structural behavior. It was also identified that the test conditions adopted directly interfere in the numerical response, which makes a standard test model necessary. Regarding the parametric study, it was identified that openings located at the edge of the column are more harmful to the slab than openings located at the apex. Regarding the position of the opening, it is clear that the closer to the column, the greater its effect in reducing the model's resistant capacity of the slab. Regarding the size of the opening, it was possible to notice that it has no direct relationship with the reduction of the load capacity. Regarding theoretical models, the Fib Model Code (2010) was the one that came closest to the numerical results, with adaptations being proposed in the normative equations of the codes NBR 6118 (ABNT, 2014), ACI 318 (2019) and Eurocode 2 (2004) for approximation of results. Finally, it was found that openings located from the pillar 3d do not significantly interfere with the structural behavior, however, there is a need to continue the parametric study to better understand the puncture phenomenon and the need for a standard test to better compare the results of different authors.